Development of 2-aminooxazoline 3-azaxanthenes as orally efficacious β-secretase inhibitors for the potential treatment of Alzheimer's disease. Issue 4 (15th February 2015) - Chen, Jian Jeffrey; Liu, Qingyian; Yuan, Chester; Gore, Vijay; Lopez, Patricia; Ma, Vu; Amegadzie, Albert; Qian, Wenyuan; Judd, Ted C.; Minatti, Ana E.; Brown, James; Cheng, Yuan; et al.
Graphical abstract